Istota due diligence prawnego w prawie polskim i amerykańskim - Śledzikowski, Marcin (Wydawnictwo Uniwersytetu Wrocławskiego, 2013)
During economic crisis, due diligence becomes very important. Although companies valuations are lower, buyers are characterized by more caution. Of their interest are companies with a solid foundation, generating steady, decent level of cash flow. Even the largest stock companies begin to count every penny. The conclusions of due diligence support the process of building and implementing the company’s market strategy and help identify potential risks to the business and legal requirements. Even if the analysis results in withdrawal from the transaction, it should be interpreted asavoidance of losses several times exceeding the cost of due diligence. We can expect that the duediligence formula will gain in popularity in the Polish reality over the next few years.
Keywords: analiza; transakcje biznesowe; prawo polskie i amerykańskie; ryzyko; uwarunkowania prawne